TRENDS IN NON-FINANCIAL MOTIVATION POLICIES OF EMPLOYEES - Costin Alexandru PANAIT; Nicoleta Georgeta PANAIT (Challenges of the Knowledge Society)
The main purpose of the paper is to identify the main non-financial motivation strategies, to emphasize their advantages and disadvantages, as well as to involve the management in achieving the motivational objectives within the organizations. Studies in the field have shown that there are a number of factors of great importance in motivating the staff that managers need to consider in improving the company's performance. Motivating human resources is not a simple process, it is complex and continuous and managers need to find the optimal mix for motivating and performance-oriented employee. Appropriate motivation of employees is the main purpose on which good management of a firm is based. Practice shows that poor leadership quality is the main cause of employee dissatisfaction that is unsatisfied with their work. Motivating staff means creating opportunities for individual and team goals, responsibility, recognition, reward, etc. Motivation implies the totality of the internal and external motives of the personality, which condition the transformation of its development potential into real and functional psychological structures and is in itself a complex and cumulative psychological system. Most reward processes are based on philosophies and reward strategies and contain policy and strategy arrangements and contain policy arrangements, principles, practices, structures and procedures that are designed and managed to deliver and maintain the types and adequate levels of benefits and other forms of reward.